Magnetic characterization and electrical field-induced switching of magnetite thin films synthesized by atomic layer deposition and subsequent thermal reduction - Zierold, Robert; Le Lam, Charlie; Dendooven, Jolien; Gooth, Johannes; Boehnert, Tim; Sergelius, Philip; Munnik, Frans; Moreno, Josep M. Montero; Goerlitz, Detlef; Detavernier, Christophe; Nielsch, Kornelius (Journal of Physics D: Applied Physics, 2014)
Magnetite (Fe3O4) of high quality was prepared by combining atomic layer deposition (ALD) with a subsequent thermal reduction process. The reduction process in hydrogen atmosphere was investigated by in situ x-ray diffraction studies as a function of temperature. A complete reduction to Fe3O4 was confirmed within a narrow temperature window during the thermal treatment. Magnetic characterization of magnetite thin films as a function of temperature, applied magnetic field and magnetic field orientation were performed. The highly stoichiometry- and impurity-sensitive Verwey transition was observed in magnetic and electrical measurements. Moreover, the isotropic point at which the magnetocrystalline anisotropy of magnetite vanishes was unveiled. Both findings prove, first, the formation of the magnetite phase against the undesired maghemite and, second, the quality of the ALD thin films to be comparable with samples grown by molecular beam epitaxy. The magnetic easy and hard axis could be found to be in-plane and out-of-plane, respectively. Consistent with angular-dependent studies of the coercive field, additionally performed first-order reversal curve measurements revealed a complex micromagnetic structure with different magnetization reversal paths for both configurations. Finally, electric field-induced resistive switching was studied in detail being in perfect agreement with results of single-crystalline samples. The presented data and its analysis support the assumption of previous works of the magnetization reversal in magnetite nanotubes, suggest improvement for future magnetization studies of nanostructures by exploiting the isotropic point and might open new paths for low-cost resistive switching devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atomic layer deposition; FORC; isotropic point; magnetite; resistive switching; thin film; Verwey transition